Cystatin C: can it be more reliable marker for estimation of glomerular filtration rate in children with reduced renal function? - YILDIZ, NURDAN (TURKISH PEDIATRICS ASSOC, 2011)
Aim: The aim of this study was to evaluate whether serum cystatin C is superior as a marker of glomerular filtration rate calculation in children with reduced renal functions. Material and Method: Serum cystatin C, creatinine and Tc-99-diethylenetriamene penta acetate (DTPA) clearance (GFRDTPA) were measured in 100 children (53 girls, 47 boys; mean age 8.4 +/- 5.1). Glomerular filtration rate was calculated by the Schwartz formula. Patients with DTPA clearance, accepted as the a gold standart, above 80 mUdk/1.73m(2) were included in group 1(n=64) and below 80 mUdk/1.73m(2) in group 2 (n=36). Receiver-operating characteristics analysis was performed to assess their diagnostic accuracy. Signed informed consents of the parents were obtained in all cases. Results: Serum cystatin C and creatinine were correlated with glomerular filtration rate in group 1 and 2. Diethylen etriamene penta acetate (DTPA) clearance was correlated with glomerular filtration rate in both groups, and with cystatin C in group 2. Receiver-operating characteristics analysis showed that the accuracy of cystatin C and glomerular filtration rate was similar. The area under curves were statistically significant but not different for cystatin C and glomerular filtration rate. Conclusions: Serum cystatin C may be useful but not superior to glomerular filtration rate calculated by Schwartz formula which is a simple and reliable method to estimate glomerular filtration rate in children with normal and decreased renal functions. (Turk Arch Ped 2011; 46: 118-23)
Keywords: Cystatin C; glomerular filtration rate; renal function; Schwartz formula; SERUM CYSTATIN; PREDICTION EQUATIONS; PLASMA CREATININE; GFR; INFANTS; LIMITATIONS; SCHWARTZ